2013
DOI: 10.1002/open.201300005
|View full text |Cite
|
Sign up to set email alerts
|

Get More Out of Your Data: A New Approach to Agglomeration and Aggregation Studies Using Nanoparticle Impact Experiments

Abstract: Anodic particle coloumetry is used to size silver nanoparticles impacting a carbon microelectrode in a potassium chloride/citrate solution. Besides their size, their agglomeration state in solution is also investigated solely by electrochemical means and subsequent data analysis. Validation of this new approach to nanoparticle agglomeration studies is performed by comparison with the results of a commercially available nanoparticle tracking analysis system, which shows excellent agreement. Moreover, it is demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 15 publications
3
83
1
Order By: Relevance
“…From the comparison between the SEM and impact data it can be concluded that both sizing methods are in very good agreement throughout the range of investigated NP sizes. This observation indicates that in contrast to previous impact analyses performed in chloride‐containing electrolytes,7, 8 no significant agglomeration—over the time frame of the experiments—of the Ag nanoparticles in the 0.1 M tri‐sodium citrate electrolyte is observed, rendering this a useful methodology for studying the size distribution of Ag nanoparticles in aqueous media.…”
Section: Summary Of the Derived Mean Radii (R) And Standard Deviationcontrasting
confidence: 54%
See 1 more Smart Citation
“…From the comparison between the SEM and impact data it can be concluded that both sizing methods are in very good agreement throughout the range of investigated NP sizes. This observation indicates that in contrast to previous impact analyses performed in chloride‐containing electrolytes,7, 8 no significant agglomeration—over the time frame of the experiments—of the Ag nanoparticles in the 0.1 M tri‐sodium citrate electrolyte is observed, rendering this a useful methodology for studying the size distribution of Ag nanoparticles in aqueous media.…”
Section: Summary Of the Derived Mean Radii (R) And Standard Deviationcontrasting
confidence: 54%
“…Previous particle coulometry investigations of silver nanoparticles have been complicated by the in situ agglomeration/aggregation of the nanoparticles 7. 8 This arises due to the requirement of relatively high ionic strengths in the electrochemical setup.…”
Section: Summary Of the Derived Mean Radii (R) And Standard Deviationmentioning
confidence: 99%
“…Beyond being an analytical technique, the direct nano‐impact method also provides a route for investigating more fundamental problems. A first example is the use of the technique for the study and monitoring of solution‐phase nanoparticle agglomeration and aggregation . In a similar vein, the magnetic‐field‐induced agglomeration of Fe 3 O 4 has also been directly evidenced .…”
Section: Section 7: Nanoparticle Voltammetrymentioning
confidence: 99%
“…Detection of dilute concentrations of pathogens is an especially important goal. The utilization of electrochemical collisions has been demonstrated to be sensitive enough to differentiate nanoparticle aggregates, such as aggregates of silver nanoparticles from monomers and dimers to higher order aggregates (26). Here, we present a technique to selectively detect viruses based on blocking and specific interactions between MCMV, an MCMV-specific antibody, and polystyrene beads (PSBs).…”
Section: Significancementioning
confidence: 99%